2021
DOI: 10.12911/22998993/141368
|View full text |Cite
|
Sign up to set email alerts
|

Methods of Dyes Removal from Aqueous Environment

Abstract: In this paper, selected methods of dyes removal from water environment were discussed, with particular attention to the adsorption method. A literature review of the latest scientific research on colour impurities removal with the use of various types of adsorbents was presented. The efficiency of the methylene blue removal process, with use of selected natural sorbents and activated carbons, was tested. The competitiveness of natural sorbents was shown. It was confirmed that these materials are efficient in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 8 publications
(8 reference statements)
0
10
0
Order By: Relevance
“…The effect that occurs with the concentration of the adsorbent of the dyes on the removal percentage and adsorption capacity among them is mentioned in several works, e.g. reported by Bożęcka [2021] where they used walnut, sunflower and rice shells, obtaining a removal percentage of various dyes up to 99%. Kakhki [2020] observed that by modifying the amount of mass of its adsorbent in the solution, the removal percentage of MO increases until obtaining 90%, although this causes a significant decrease in the adsorption capacity.…”
Section: Thermodynamic Analysis Of the Of Mb And Mo Adsorption Processmentioning
confidence: 99%
See 3 more Smart Citations
“…The effect that occurs with the concentration of the adsorbent of the dyes on the removal percentage and adsorption capacity among them is mentioned in several works, e.g. reported by Bożęcka [2021] where they used walnut, sunflower and rice shells, obtaining a removal percentage of various dyes up to 99%. Kakhki [2020] observed that by modifying the amount of mass of its adsorbent in the solution, the removal percentage of MO increases until obtaining 90%, although this causes a significant decrease in the adsorption capacity.…”
Section: Thermodynamic Analysis Of the Of Mb And Mo Adsorption Processmentioning
confidence: 99%
“…Industries such as cosmetics, food, biomedicine, paper, and textiles use dyes to produce their products generating around 10 thousand tons/year of waste [Uddin et al, 2021;Amalraj et al, 2021;Kadhom et al, 2020]. This has caused several problems due to toxicity, low biodegradation on the entire ecosystem around this discharge of the dyes due to their direct interference in the photosynthesis process, in addition to causing various diseases to humans in the skin and respiratory system [Panneerselvam et al, 2021;Marquez et al, 2021;Amalraj et al, 2021;Bożęcka et al, 2021]. Dyes are divided into anionic (acid dyes), nonionic (dispersed) and cationic (basic dyes), among them are methyl orange (MO) and methylene blue (MB) which have a similar molecular mass [Kadhom et al, 2020;Lacin et al, 2020;Uddin et al 2021].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…ere are three types of dyes: anionic, cationic, and nonionic. Anionic dyes are classified as direct, acid, and reactive dyes, whereas cationic dyes can be considered basic dyes [6]. Recently, significant interest has centred on the elimination of dyes from wastewater due to their resistance to biodegradation and their hazardous nature [4].…”
Section: Introductionmentioning
confidence: 99%